Anisotropic tomography of heavy quark dissociation by using the general propagator structure in a finite magnetic field - Ghosh, Ritesh; Bandyopadhyay, Aritra; Nilima, Indrani; Ghosh, Sabyasachi (Physical review, 2022)
In this work we have explored the imaginary part of the heavy quark potential and subsequently the dissociation of heavy quarkonia at finite temperature and in a magnetic field. With respect to earlier investigations on this topic, the present work contains three new ingredients. The first one is considering all Landau level summations, for which the present work can be applicable in the entire magnetic field domain - from weak to strong. The second one is the general structure of the gauge boson propagator in a hot magnetized medium, which is used here in the heavy quark potential problem for the first time. The third one is a rich anisotropic structure of the complex heavy quark potential, which explicitly depends on the longitudinal and transverse distance. By comparing with earlier references, we have attempted to display our new contributions by plotting heavy quark potential tomography and dissociation probability at finite temperature and in a magnetic field.
Gesehen am 03.01.2023